Morphological Analysis of the Human Internal Iliac Artery in South Indian Population - Naveen NS; Murlimanju BV; Vishal Kumar; Jayanthi KS; Krishna Rao; Thejodhar Pulakunta (Online Journal of Health & Allied Sciences, 2011)
Objectives: The accidental hemorrhage is common due to erroneous interpretation of the variant arteries during surgical procedures, hence the present study has been undertaken with reference to its morphological significance. The objectives were to examine the level of origin, length and the branching pattern of the human internal iliac artery in South Indian population. Methods: The study included 60 human bisected pelvises irrespective of their side and sex. The specimens were collected from the anatomy laboratory and were fixed with the formalin. The branching patterns were studied and demonstrated as per the guidelines of Adachi. Results: The origin of internal iliac artery was at the level of S1 vertebra in majority (58.3%) of the cases. The average length of internal iliac artery was 37 ± 4.62 mm (range, 13-54 mm). The type I pattern of the internal iliac artery was most common (83.5%) followed by types III and II. The type IV and V pattern of adachi were not observed. Conclusions: The results of this study were different from those reported by others and may be because of racial and geographical variations. Prior knowledge of the anatomical variations is beneficial for the vascular surgeons ligating the internal iliac artery or its branches and the radiologists interpreting angiograms of the pelvic region.